The eIF2 kinase PERK and the integrated stress response facilitate activation of ATF6 during endoplasmic reticulum stress - Teske, Brian F. (The American Society for Cell Biology, 2011)
Disruptions of the endoplasmic reticulum (ER) that perturb protein folding cause ER stress and elicit an unfolded protein response (UPR) that involves translational and transcriptional changes in gene expression aimed at expanding the ER processing capacity and alleviating cellular injury. Three ER stress sensors (PERK, ATF6, and IRE1) implement the UPR. PERK phosphorylation of the α subunit of eIF2 during ER stress represses protein synthesis, which prevents further influx of ER client proteins. Phosphorylation of eIF2α (eIF2α∼P) also induces preferential translation of ATF4, a transcription activator of the integrated stress response. In this study we show that the PERK/eIF2α∼P/ATF4 pathway is required not only for translational control, but also for activation of ATF6 and its target genes. The PERK pathway facilitates both the synthesis of ATF6 and trafficking of ATF6 from the ER to the Golgi for intramembrane proteolysis and activation of ATF6. As a consequence, liver-specific depletion of PERK significantly reduces both the translational and transcriptional phases of the UPR, leading to reduced protein chaperone expression, disruptions of lipid metabolism, and enhanced apoptosis. These findings show that the regulatory networks of the UPR are fully integrated and help explain the diverse biological defects associated with loss of PERK.